Preclinical evaluation of racotumomab, an anti-idiotype monoclonal antibody to N-glycolyl-containing gangliosides, with or without chemotherapy in a mouse model of non-small cell lung cancer - Segatori, Valeria Inés (2012)
N-glycolylneuraminic acid (NeuGc) is a sialic acid molecule usually found in mammalian cells as terminal constituents of different membrane glycoconjugates such as gangliosides. The NeuGcGM3 ganglioside has been described as a tumor antigen for non-small cell lung cancer (NSCLC) in humans. Racotumomab is an anti-NeuGc-containing gangliosides anti-idiotype monoclonal antibody (formerly known as 1E10) that has received attention as a potential active immunotherapy for advanced lung cancer in clinical trials. In this work, we have examined the antitumor activity of racotumomab in combination or not with chemotherapy, using the 3LL Lewis lung carcinoma as a preclinical model of NSCLC in C57BL/6 mice. Vaccination with biweekly doses of racotumomab at 50-200 μg/dose formulated in aluminum hydroxide (racotumomab-alum vaccine) demonstrated a significant antitumor effect against the progression of lung tumor nodules. Racotumomab-alum vaccination exerted a comparable effect on lung disease to that of pemetrexed-based chemotherapy (100 mg/kg weekly). Interestingly, chemo-immunotherapy was highly effective against lung nodules and well tolerated, although no significant synergistic effect was observed as compared to each treatment alone in the present model. We also obtained evidence on the role of the exogenous incorporation of NeuGc in the metastatic potential of 3LL cells. Our preclinical data provide support for the combination of chemotherapy with the anti-idiotype monoclonal antibody racotumomab, and also reinforce the biological significance of NeuGc in lung cancer.